Contribuição às estratégias de controle para sistemas distribuídos de potência - Oberto, Victor Paula (2013)
A distributed power supply composed of multiple DC-DC converters connected in parallel offers several advantages in comparison to a centralized solution. Among these benefits are the following: redundancy, system modularity, increased reliability, improved thermal ow on the system and reduction in the physical size of the units. Its main purpose is to evenly share the output current between the converters. In practice, this specification is rarely achieved without the use of a specific control strategy for sharing, since each converter produces output dependent on the tolerances of the components and the line impedance that connects the unit to the load bus. This imbalance in the shared current can cause excessive stress on the units operating outside of their specifications, increasing their chances of failure. Also, it is desirable that any points of failure are minimized or eliminated by adopting a decentralized control strategy, minimizing connections between units. In this work, the generalized model of output current for a i -th converter from a source with n converters connected in parallel is obtained. To obtain this model, each converter present in the system is modeled as a controlled voltage source, connected to the load bus through an individual line resistance. As the main contribution, two strategies to control current sharing between converters are proposed, based on parallelism without communication between modules, specifically the droop control. To validate the design, the simulation results for a power supply containing three converters in parallel applied to a LED street lamp fixture are shown and analyzed. At the end of this document, the conclusions and suggestions for future work involving the subject are developed.